2003
DOI: 10.1590/s0102-311x2003000400013
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of retrovirus (HTLV) infection among Indian populations in the Amazon Region of Brazil

Abstract: HTLV was initially described in association with a form of leukemia in Japan and a neurological disease in the Caribbean. It was soon shown that HTLV-II was endemic among Amerindians and particularly among Brazilian Indians. The Amazon Region of Brazil is presently the largest endemic area for this virus and has allowed several studies concerning virus biology, the search for overt disease, epidemiological data including detailed demographic data on infected individuals, clear-cut geographic distribution, defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
0
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 64 publications
1
49
0
8
Order By: Relevance
“…Regarding our previous study that did not identified HTLV-1 infection in other Amazonian populations composed by descendents of African slaves (Ishak et al 2003), the current results represent the first report of HTLV-1 infection in a mocambo located in the Brazilian Amazon region. Furthermore, the presence of HTLV-1 in this geographical area is of paramount importance because of the previous description of a cluster of cases of TSP/HAM in two individuals residing in Cachoeira do Arari county, Marajó Island (Ishak et al 2002).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Regarding our previous study that did not identified HTLV-1 infection in other Amazonian populations composed by descendents of African slaves (Ishak et al 2003), the current results represent the first report of HTLV-1 infection in a mocambo located in the Brazilian Amazon region. Furthermore, the presence of HTLV-1 in this geographical area is of paramount importance because of the previous description of a cluster of cases of TSP/HAM in two individuals residing in Cachoeira do Arari county, Marajó Island (Ishak et al 2002).…”
supporting
confidence: 59%
“…HTLV-1 is endemic worldwide and HTLV-2 infection has been shown to be endemic in native American Indian populations (Hall et al 1992, Ishak et al 1995. In Brazil, particularly in the Amazon region, HTLV-1 and HTLV-2 infections have been found among urban and rural populations with relevant endemicity (Ishak et al 1995, 2003, Vallinoto et al 1998). The molecular epidemiology has been well established concernig HTLV-2 infection and it has shown the occurrence of a new molecular subtype named HTLV-2c (Ishak et al 1995).…”
mentioning
confidence: 99%
“…HTLV-2 is prevalent in native populations, such as indigenous peoples in the Americas and Pygmy tribes in Africa, and in intravenous drug users [15][16][17][18][19] . Despite a 65% homology with HTLV-1, HTLV-2 has not been consistently associated with human disease; however, neurological disorders similar to HAM/TSP have been observed in patients with HTLV-2 infection 15,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, HTLV-1 is also endemic among Amerindians in Peru, a population thought to be infected with HTLV-2 in several countries of Latin America 7,13,19,22 . Nevertheless, HTLV-2 was only detected in two Peruvian Amazonian Indians and in several MSM from Peru 19,28 .…”
mentioning
confidence: 99%